METHODOLOGY FOR THE EXAMINATION OF JEWELRY ITEMS MOUNTED WITH NATURAL TREATED DIAMONDS FOR THE PURPOSES OF FORENSIC CONSUMER GOODS EVALUATION - A. Selivanov (Теория и практика судебной экспертизы, 2015)
.